2012
DOI: 10.4314/as.v10i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Actions of Some Botanicals to Storage Bruchid, Callosobruchus Maculatus (F.) on Stored Cowpea (<i>Vigna unguiculata</i> L. WALP.) Ogbaji Moses and Osuman Dorathy

Abstract: INSECTICIDAL ACTIONS OF SOME BOTANICALS ON STORAGE BRUCHID, Callosobruchus maculatus (F.) OF STORED COWPEA (Vigna unguiculata L. WALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Storage of harvested produce of any kind is important for food conservation and management (Yallappa et al, 2011). It has been recognized that plant species play an important role in the preservation of harvested produce by exerting pesticidal properties and or biological activity against a wide range of pests (Khatun, 2011;Ogbaji and Osuman (2011). Neem (Azadirachta indica) materials among others have been well reported by many researchers as grain protectants against grain storage insects (Jilani and Su, 1983;Yadar, et al, 2007;Khatun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Storage of harvested produce of any kind is important for food conservation and management (Yallappa et al, 2011). It has been recognized that plant species play an important role in the preservation of harvested produce by exerting pesticidal properties and or biological activity against a wide range of pests (Khatun, 2011;Ogbaji and Osuman (2011). Neem (Azadirachta indica) materials among others have been well reported by many researchers as grain protectants against grain storage insects (Jilani and Su, 1983;Yadar, et al, 2007;Khatun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that agricultural extension services are more accessible to male farmers than rural women farmers in Nigeria. Osuman (1997) reported that staff of agricultural extension services are mostly men, and are tend to giving help to men. Morna (1989) reported that agricultural extension workers interact with men in their visit to rural areas, and not women in Malawi, they interact with men on areas of improved technologies, and access to agricultural inputs.…”
Section: Introductionmentioning
confidence: 99%